Regression Analysis of Ground Water Quality Data of Old Aurangabad City (Maharashtra) - Ubale, M.B.; Farooqui, Mazahar; Md. Arif, Pathan; Zaheer, Ahmed; Dhule, D.G. (Asian Journal of Chemistry, 2010)
Ground water samples from different places of old Aurangabad city (Maharashtra) have been analyzed for various water quality constituents during 1998 and correlation coefficients among different parameters determined. A regression equation to predict the concentration of water quality constituents having significant correlation coefficients with oxidation-reduction potential (ORP) and the usefulness of their equations in predicting the ground water quality have been discussed.